Same Problems, Different Projects: Do the Same Solutions Work? - Duarte, Paulo; Sousa, Amanda; Silva, Jefferson Carvalho; Santos, Ismayle; Fernandes, Marina Reis; Vasconcelos, Danilo Reis; Francisco, Mariana Salamoni; Andrade, Rossana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Software requirements management is a process that involves several activities that generate artifacts that serve as a basis for project development. This process occurs continuously and is responsible for performing analysis, tracking, documentation, prioritization and change control so that there is agreement on the requirements between all parties involved. However, these activities are not trivial and their form of execution varies according to the nature of each project. With this in mind, teams should be able to identify points for improvement, such as applying new practices, new technologies or tools and allocating resources to make the process more optimized and more productive. The paper presents an experience report related to the identification and application of improvements and good practices within two software development projects inside the same research group. In the first project, we address problems involving software requirements. In the second one we address the problem involving the measurement of the size of tasks. Both projects target to release the same “bigger” application but each one develops a minor part of it. Finally, difficulties and lessons learned, in relation to the changes made in the current requirements management process in both projects, are presented.